2012
DOI: 10.1016/j.chom.2012.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Tetherin/BST-2 Is Essential for the Formation of the Intracellular Virus-Containing Compartment in HIV-Infected Macrophages

Abstract: SUMMARY HIV-1 assembly and release occurs at the plasma membrane in T lymphocytes, while intracellular sites of virus assembly or accumulation are apparent in macrophages. The host protein tetherin (BST-2) inhibits HIV release from the plasma membrane by retaining viral particles at the cell surface, but the role of tetherin at intracellular HIV assembly sites is unclear. We determined that tetherin is significantly upregulated upon macrophage infection and localizes to an intracellular virus-containing compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
96
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(111 citation statements)
references
References 49 publications
12
96
3
Order By: Relevance
“…8A and B). We did not observe tethers greater than 37 nm in length, as seen in selected images of chemically fixed samples imaged by conventional TEM (32,36,37). The distance between tethered virions was the same for mature (17.8 Ϯ 7.24 nm) and immature virions (17.9 Ϯ 6.31 nm), which suggests that HIV-1 maturation does not influence the length of the tether.…”
Section: Clem and Cryo-et Of Hiv-1 Vlps Tethered To Human Cellsmentioning
confidence: 68%
See 2 more Smart Citations
“…8A and B). We did not observe tethers greater than 37 nm in length, as seen in selected images of chemically fixed samples imaged by conventional TEM (32,36,37). The distance between tethered virions was the same for mature (17.8 Ϯ 7.24 nm) and immature virions (17.9 Ϯ 6.31 nm), which suggests that HIV-1 maturation does not influence the length of the tether.…”
Section: Clem and Cryo-et Of Hiv-1 Vlps Tethered To Human Cellsmentioning
confidence: 68%
“…Immunoelectron microscopy studies have shown tetherin staining on viral membranes and on the host cell plasma membrane near sites of HIV-1 budding (23,32,37,38). Electron-dense fibrous material linking HIV-1 to the host cell membrane (37) and to virus-containing compartments in macrophages was observed (36). However, the length of these tethers (between 50 and 100 nm), which was inferred from TEM two-dimensional (2D) projection images and not 3D volumes, exceeded the length predicted by either tetherin model by an order of 3-to 6-fold.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…BST‐2 may enhance cell‐to‐cell viral spread by the formation of viral clusters 50. However, inhibition of cell‐to‐cell viral spread by BST‐2 could occur by initiation of virological synapses, by trapping viruses in intracellular compartments 51, 52, 53, or by eliciting antibody‐dependent cellular cytotoxicity (ADCC) 54, 55, 56 (Fig.…”
Section: Bst‐2/tetherin: Roles In Viral Pathogenesismentioning
confidence: 99%
“…ϩ T cells, in part due to differences in the level of expression of retroviral restriction factors, such as tetherin, SAMHD1, and APOBEC3 (20)(21)(22). SAMHD1 specifically contributes to the lower concentration of deoxynucleoside triphosphates already found in macrophages, greatly inhibiting reverse transcription (23,24).…”
mentioning
confidence: 99%